FACTORS AFFECTING COMPLIANCE PERSONAL TAX PAYABLE WITH SANCTIONS AS A MODERATED VARIABLES (Case Study at KPP Pratama Medan Polonia) - Sinaga, Bima (International Journal of Public Budgeting, Accounting and Finance, 2021)
This study aims to determine the effect awareness, environment, tax services, knowledge of taxation, tax audit and tax collection on individual taxpayer compliance at KPP Pratama Medan Polonia. In addition, this study will also test whether sanctions can be used as a moderating variable in the research model. This type of research is a causal associative research. This research conducted in KPP Pratama Medan Polonia, North Sumatra Province. The data collection method used is a questionnaire method given to research respondents. The number of samples in this study were 99 people who were obtained by calculating the Slovin formula. The type of data used in this study is primary data. The data analysis method used is to use Multiple Linear Regression Analysis and Interaction Test. Data processing in this study was carried out with the help of SPSS 25 software. The results obtained in this study indicate that awareness, tax services and tax audits have a positive and significant effect on taxpayer compliance. Furthermore, it can also be seen that tax sanctions can moderate the influence of the tax environment and tax services on individual taxpayer compliance at KPP Pratama Medan Polonia.